Data processing intervals through dynamical models applied to the analysis of self-degenerative systems - Ferreyra, Ricardo Tomás (2015)
Fil: Ferreyra, Ricardo Tomás. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.